2019
DOI: 10.1111/jch.13629
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of early intensive antihypertensive treatment on rebleeding and perihematomal edema in acute intracerebral hemorrhage

Abstract: To observe the effect of early intensive blood pressure (BP)–lowering treatment on rebleeding and perihematomal edema (PE) in patients with acute intracerebral hemorrhage (ICH). A total of 121 patients with ICH were randomly assigned to an early intensive antihypertensive treatment group (IG) (n = 62) or control group (CG) (n = 59). For both groups, 25 mg of urapidil injection was slowly administered intravenously in 6 hours of the onset. For the IG, 100 mg of urapidil and 30 mL of 0.9% sodium chloride were th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The intensive strategy resulted effective to reduce re‐bleeding and perihematomal edema in comparison to control and was associated to better short‐term functional outcome as assessed by National Institutes of Health Stroke Scale scores and Barthel Index up to 90 days . There was no significant difference in mortality between the two groups …”
Section: Targeting Blood Pressure In Cerebral Hemorrhagementioning
confidence: 92%
See 3 more Smart Citations
“…The intensive strategy resulted effective to reduce re‐bleeding and perihematomal edema in comparison to control and was associated to better short‐term functional outcome as assessed by National Institutes of Health Stroke Scale scores and Barthel Index up to 90 days . There was no significant difference in mortality between the two groups …”
Section: Targeting Blood Pressure In Cerebral Hemorrhagementioning
confidence: 92%
“…In both groups, 25 mg of urapidil injection was slowly administered intravenously in 6 hours from the onset; 100 mg of urapidil was further slowly administered via micropump in the intensive arm . The intensive strategy resulted effective to reduce re‐bleeding and perihematomal edema in comparison to control and was associated to better short‐term functional outcome as assessed by National Institutes of Health Stroke Scale scores and Barthel Index up to 90 days . There was no significant difference in mortality between the two groups …”
Section: Targeting Blood Pressure In Cerebral Hemorrhagementioning
confidence: 99%
See 2 more Smart Citations
“…A recent study has shown that intensive BP control is associated with a decreased perihematomal edema expansion rate (PHER) at 24 hours in deep ICH, which in turn is associated with adverse outcomes in basal ganglia ICH but not in all deep ICH (e.g., thalamic ICH) [ 144 ]. Another randomized controlled trial study revealed that the volume of the hematoma at 24 hours, the volume of PHE at 72 hours, and the NIHSS scores at 30 and 90 days in patients receiving intensive antihypertensive treatment were lower than those of the placebo group, while the Barthel scores at 30 and 90 days were higher [ 225 ]. Furthermore, a study with 635 ICH patients illustrated that angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers reduced mortality, volume of perihematomal edema, and prevalence of pneumonia in patients with hypertension [ 226 ].…”
Section: Potential Therapeutic Targets For Phe After Ichmentioning
confidence: 99%